2021
DOI: 10.1177/10506519211044195
|View full text |Cite
|
Sign up to set email alerts
|

Curricular Efforts in Technical Communication After the Social Justice Turn

Abstract: The social justice turn in technical and professional communication (TPC) has inspired a substantial body of progressive scholarship and discussion. But it is not clear how these scholarly efforts have shaped (or are shaping) programmatic and curricular efforts. This article reports the findings of a survey of TPC instructors and an analysis of 231 TPC programs to examine their curricular efforts toward social justice. Drawing from the mixed findings, the authors argue that vigorous curricular efforts in socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Other research found that students entering the workplace have knowledge gaps in business operations, problem-solving in industry, and project management (Stanton, 2017; Whiteside, 2003; Wilson & Ford, 2003). Some of these topics are not central to university pedagogies because it takes time for university curricula to integrate research focuses into pedagogy (Agboka & Dorpenyo, 2022; Dubinsky & Getchell, 2021). And areas such as business operation practices and the intricacies of industry problem solving would always be difficult to fully integrate into university curricula, given the diversity of TPC workplaces and the fast-paced changes in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Other research found that students entering the workplace have knowledge gaps in business operations, problem-solving in industry, and project management (Stanton, 2017; Whiteside, 2003; Wilson & Ford, 2003). Some of these topics are not central to university pedagogies because it takes time for university curricula to integrate research focuses into pedagogy (Agboka & Dorpenyo, 2022; Dubinsky & Getchell, 2021). And areas such as business operation practices and the intricacies of industry problem solving would always be difficult to fully integrate into university curricula, given the diversity of TPC workplaces and the fast-paced changes in industry.…”
Section: Introductionmentioning
confidence: 99%